Challenges in the Automation of Eddy Current Evaluation for Aerospace‐Spacecraft Propellant Tanks. (4th December 2019) - Poornima, S; Ramprasad, B; Ingersol, S; Narayan, R; Narayanan, G
Abstract: An automated system is designed for Eddy current evaluation of spacecraft components with a proven multi‐axis industrial robot interfaced with dynamic electromechanical distance compensation device (EMDC), automated probe exchange, array eddy current probe, precision component fixtures and turntables, eddy current equipments, centralized control system to control robot and eddy current system with seamless handshake capability. Accuracy of the probe guidance system for the entire test period is ensured by the repeatable probe positioning within ±0.05mm by the robot and a minimal lift off error of ± 50μ, achieved by deploying an automated device with a high precision component turntable with positioning accuracy of £0.005°. The component is aligned initially by LASER and fine alignment is established by Infrared based touch‐tool. Automation of eddy current based evaluation technique has made the system state of the art with high probability of defect detection capability at a lesser evaluation time. Also the system has enhanced process confidence level due to the high positional accuracy of the system in comparison with manual methods, with defect detection capabilities up to depth of 0.12mm on a shell of 0.8 mm thickness. The challenges in automation of the system include intricacies due to component's thickness and also due to the complex hemispherical profile of the component. Fixtures were designed to provide enough support for the fragile components with soft pads at the contact area, and alignment of component in turntable to avoid surface run‐out errors, synchronization between turntable and the robot scanning speed, precision maintenance of lift‐off distance between eddy current probe and component surface, array eddy current probe design with multiple elements ensuring defect detection in any orientation are some of the challenges overcome in the automation of eddy current evaluation technique. The challenges in designing an automated eddy current system for evaluation of propellant tanks were systematically overcome with automation to get better defect characterization capability with reduced test time aiding in design optimization of thin walled metallic structures like propellant tanks.